Sex differences in support leg dynamics in soccer instep kicking - Iitake, T.; Iwasaki, R.; Nunome, H. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The present study aimed to demonstrate differences in the support leg knee joint dynamics during soccer instep kicking between female and male players. Three-dimensional lower body motion (500 Hz) and ground reaction force underneath the support leg (1000 Hz) during the instep kicking of twenty female and twenty male players, were captured to calculate knee joint torque and joint power of the support leg using inverse dynamics. Statistical Parametric Mapping (SPM) was conducted to compare these time-series changes. Female players exhibited significantly smaller knee extension joint torque (58~100%, p<0.001) and joint power (82~100%, p=0.001) than male players. Our findings suggested a possible strategy for achieving a better instep kicking of female players by enhancing the knee extensor`s strength of the support leg.